Stylistics : A Contact between Linguistics and Literary Criticism (Journal of the College of Basic Education, 2023)
Quirk (1969) has remarked that a man's style is as specific as hisfingerprints. Stylistic analysis can in fact settle many knotty problems inltterature. A Writer's use of language, if studied carefully , can reveal hisaesthetic personality , his deep – laid philosophy and world – view , theway he looks at the world , perhaps far more accurately than any study ofhis background and the literary movement he subscribes to . In fact , thequestion of the nature of stylistics , and its position among the variousdisciplines, its scope and its limits have aroused considerable discussion.The term "stylistics" can apply to various kinds of linguistic analysis.Anyhow, stylistics, which is, in general, incorporated within theterminology of linguistics, has not won the satisfaction of some linguists.therefore, they began to coin some other new terms . Thus, this researchis intended to present discussion of the scope of stylistics, stylisticanalysis, and stylistics as a middle ground between linguistics and literarycriticism. In general, it is divided into three parts each to cover a certainaspect of the subject .the first part is a review of the definition ofstylistics, its function, and its aims. The second part is concerned withstylistic analysis and kinds of stylistic studies. Whereas, the third part ofthis research discusses the role of stylistics as a contact betweenlinguistics and literary criticism.